Electromyographic analysis pf the deltoid muscle during various shoulder exercises - Sweeney, Samantha P. (My University, 2014)
The purpose of this study was to determine which exercise activates the deltoid muscle to the greatest degree using electromyographic (EMG) analysis. Sixteen experienced male lifters completed five repetitions of the following exercises using 70% of 1 RM, body weight, or a rope for resistance: dumbbell (DB) shoulder press, DB front raise, bent arm lateral raise, seated rear lateral raise, cable diagonal raise, push-ups, battling ropes, barbell upright row, 45 degree incline row, and dips. Surface EMG was recorded and represented as a percentage of the maximal voluntary contraction. A one-way ANOVA with repeated measures was used to test for differences in EMG between exercises. Anterior deltoid analysis showed a significant difference in muscle activation between the DB shoulder press and the other nine exercises. Middle deltoid analysis showed no significant difference between the 45 degree incline row and bent arm lateral raise while all other exercises elicited significantly lower muscle activation. Posterior deltoid analysis showed no significant difference between the seated rear lateral raise and 45 degree incline row while all other exercises elicited significantly lower muscle activation. Based on the musculature of the deltoid and the findings of this study, a variety of exercises are needed to effectively train the deltoid. Further research investigating shoulder exercises not tested in this study is still needed.
Keywords: Shoulder--Research; Exercise--Health aspects; Weight training--research